Analisis Pengaruh Rasio Keuangan Terhadap Nilai Profit Sharing Deposito Mudharabah Perbankan Syariah Di Indonesia dan Malaysia Tahun 2017 – 2023: Tahun 2017 – 2023 - Lala Supriyati; Mukti Wibowo; Anugrah Fitria Berliannanda (Journal Of Islamic Economics And Finance, 2024)
The study aims to determine the impact of return on assets, return on equity, operating costs and operating revenue, financing to deposit ratio, and non- performing finance on the value of the profit sharing of Mudharabah deposits. The sample of this research is Shariah General Bank, registered with the Indonesian Financial Services Authority and the Bank of Malaysia State in 2017– 2023. The results of research at the Shariah General Bank in Indonesia show that the variable Return on Assets has a negative and significant impact on the value of the profit sharing of deposits. While the variables Return on Equity, Operational Costs and Operational Revenue, Financing to Deposit Ratio, and Non-Performing Finance do not have an effect on the profit sharing value of deposit deposits, the results of the study at the Shariah General Bank in Malaysia show that return on assets and return on equity have an influence on the share value of the profit of the deposit.